Design and Implementation of Web-based Church Information Systems (Case Study : HKBP Kebon Jeruk) - Armando Ondihon Kristoper Purba; Supardi Supardi; Ernawati Dewi; Meilieta Anggriani Porrie; Muhammad Syafrullah (IAES Indonesia Section, 2019)
HKBP Kebon Jeruk Church has a lot of data consisting of church data, Pastor data, Church server data, family data, marital data, baptismal data, and also about church agenda such as the schedule of activities Church, schedule of church service. The problem in HKBP Kebon Jeruk is that the Data is provided and managed manually, as well as difficulties in finding the necessary information. Therefore, the system needs to be built by the HKBP Kebon Jeruk Church to request church management data.The method used in the HKBP Kebon Jeruk system is the Extreme Programming method, and the analysis used is the PIECES analysis. The result of this research is to build the HKBP Kebon Jeruk system according to the needs of the user.